THE ROLE OF CITIES IN ENDING VIOLENCE AGAINST CHILDREN IN SOUTH AFRICA - Fambasayi, Rongedzayi; Katsidzira, Rejoice Shamiso (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
The global development agenda acknowledges the role of cities in achieving the United Nations’ Sustainable Development Goals (SDGs) and addressing contemporary challenges caused by urbanization. SDG 11 aspires to make “cities inclusive, safe, resilient and sustainable” by 2030, even as the global urban population continues to grow exponentially, along with — even more rapidly — the population of children living in cities. Cities are the level of government closest to people’s daily lives, and are best placed to address the numerous challenges and rights violations that children are exposed to, including sexual exploitation and abuse, violence, trafficking, and child labour. SDG 16.2 has the primary aim of ending the “abuse, exploitation, trafficking and all forms of violence against children”. Through the lens of the subsidiarity principle, this article argues that localization to the city level of law and policy strategies that address violence against children can provide normative and powerful legal tools for their protection. Although there is developing scholarly literature on the global aspirations expressed in SDG 11 and SDG 16.2, little has been offered from a child rights perspective on the role of city governments in the prevention of, and protection of children from, violence.